PERANAN ORANG TUA DALAM MEWUJUDKAN 10 (SEPULUH) HAK-HAK ANAK MENURUT PERSFEKTIF ISLAM - Rabiatul Adawiyah (Jurnal Pengabdian Mitra Masyarakat, 2023)
Humans are created as social beings, humans cannot live alone, because humans need interaction with one another. Humans must obey the rules of social norms. There are several definitions of Social Beings. According to the Big Indonesian Dictionary, Social Beings are humans who have reciprocal relationships with other humans. Meanwhile, according to DR. Elly M. Setiadi, explained that Social Beings are beings who in their lives cannot escape the influence of others. Likewise, a child needs the role of his parents as a place of protection, education, and supervision.  According to Suryono Sukanto (1985, p 268), explains that the role is a very dynamic position in aspects of life. A person has carried out his rights and obligations in carrying out a role based on his position in society. Meanwhile, according to the Big Indonesian Dictionary (2005, p 802),   parents have the meaning of biological father or biological mother, some are interpreted as older people because of their intelligence,  intelligence or expertise. The role of parents is very important in a child's life. Islam teaches that there are several things related to the role of parents in providing children's rights.